2019
DOI: 10.3390/su11113088
|View full text |Cite
|
Sign up to set email alerts
|

Customer Incentive Rebalancing Plan in Free-Float Bike-Sharing System with Limited Information

Abstract: Free-float bike-sharing (FFBS) systems have increased in popularity as a sustainable travel mode in recent years, especially in the urban areas of China. Despite the convenience such systems offer to customers, it is not easy to maintain an effective balance in the distribution of bikes. This study considers the dynamic rebalancing problem for FFBS systems, whereby user-based tactics are employed by incentivizing users to perform repositioning activities. Motivated by the fact that the problem is frequently fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 62 publications
(70 reference statements)
0
7
0
Order By: Relevance
“…For optimising operation strategies, the fleet management was the main approach of bike-sharing systems, focusing on distributing and repositioning bikes between stations, i.e., rebalancing the fleet within the system [72,82,101,150,175,179,182,191,192]. Wu et al [179] sought to elaborate an incentive plan for users to perform the repositioning activities, Fan et al [182] sought to determine the fleet size, while Zhang et al [82], Cao and Xu [192] and Zhou et al [101] elaborated repositioning plans, including routes, scheduling of the operation [82] and number of bicycles [192]. The study of Chang et al [84] distinguishes itself by incorporating damaged bicycles into the model.…”
Section: A Planning and Policy-makingmentioning
confidence: 99%
“…For optimising operation strategies, the fleet management was the main approach of bike-sharing systems, focusing on distributing and repositioning bikes between stations, i.e., rebalancing the fleet within the system [72,82,101,150,175,179,182,191,192]. Wu et al [179] sought to elaborate an incentive plan for users to perform the repositioning activities, Fan et al [182] sought to determine the fleet size, while Zhang et al [82], Cao and Xu [192] and Zhou et al [101] elaborated repositioning plans, including routes, scheduling of the operation [82] and number of bicycles [192]. The study of Chang et al [84] distinguishes itself by incorporating damaged bicycles into the model.…”
Section: A Planning and Policy-makingmentioning
confidence: 99%
“…A stochastic simulation optimization model, which adopted a rank and search methodology, was used to maintain expected satisfactory service levels while maximizing total expected daily profit. Their findings suggested that an optimal incentive-based rebalancing plan could achieve higher bike utilization [33].…”
Section: Related Workmentioning
confidence: 99%
“…Reiss and Bosenberger [18] studied a user-based approach to a FFBS system and discussed the advantages and applicable scenarios for both operator-based and user-based relocation strategies. Wu et al [19] employed user-based tactics by incentivizing users to perform repositioning activities and constructed a more detailed quantitative model which can derive the optimal incentive scheme for the FFBS system. Some studies considered both user-based and operatorbased strategies.…”
Section: E User-based Strategiesmentioning
confidence: 99%